2020
DOI: 10.4012/dmj.2019-151
|View full text |Cite
|
Sign up to set email alerts
|

Future prospects of zirconia for oral implants —A review

Abstract: Zirconia have been applied to dental implants as well as fixed dental prostheses due to their mechanical, esthetic and biocompatible performance. Moreover, they offer an advantage over titanium (Ti) implants, in that there is no risk of discoloration or hypersensitive reaction with allergy. In this review, the durability and tissue-compatibility of zirconia for the oral implants was mainly discussed. Hot isostatic pressing of Y-TZP had higher cyclic fatigue strength than Cp-Ti (Grade-2), leading the sufficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 47 publications
1
33
0
Order By: Relevance
“…It has been reported that it is possible to clean the prosthesis before it is placed in the oral cavity and activate its properties, and it is effective in improving the bond between zirconia and the resin adhesive [94]. By improving hydrophilicity, it also has the effect of improving cell adhesion, but there is a problem with the sustainability of this effect, and, if left in the air, it will return to its original state within a few days [95].…”
Section: Plasma Irradiationmentioning
confidence: 99%
“…It has been reported that it is possible to clean the prosthesis before it is placed in the oral cavity and activate its properties, and it is effective in improving the bond between zirconia and the resin adhesive [94]. By improving hydrophilicity, it also has the effect of improving cell adhesion, but there is a problem with the sustainability of this effect, and, if left in the air, it will return to its original state within a few days [95].…”
Section: Plasma Irradiationmentioning
confidence: 99%
“…Some patients even develop metal hypersensitivity issues with titanium dental implants [9][10][11][12]. Nowadays, zirconia-based ceramics are considered as the most promising alternatives to titanium in dentistry because of their tooth-like color, excellent biocompatibility, and acceptable mechanical properties [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…They reported that both therapies were effective for short-time clinical improvements, but that a complete disease resolution was not achieved by these therapies. Yoshinari [63] suggested that modification with fluoride or antimicrobial peptide and/or atmospheric-pressure plasma irradiation will be useful for antimicrobial surface modifications of the zirconia implants. Further studies should be needed for cleaning the blastedHF+UV zirconia surface.…”
Section: Discussionmentioning
confidence: 99%